Design the Enterprise Architecture Model TOGAF 9.2 for PT Service Applications Management at PT. XXX - Widiadnyana, Putu; Andreyana, Putu Veda (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 1 (2024): JITTER, Vol.5, No.1, April 2024, 2024)
Enterprise architecture has an important role in supporting business goals in the ever-growing digital era. Research on PT service applications. XXX, where qualitative research methods are used, involves interviews with Heads of companies. This approach refers to basic architectural theory andenterprise architecture, by usingframework TOGAF for analysis. Through stagesPreliminary untilArchitecture Change Management, TOGAF ADM version 9.2 is implemented to design the relevant architecture. The research results provide architectural design of service applications and demonstrate IT creationRoadmap which becomes a recommendation based on the company architecture objectives that have been set.